Utilization of Plastic Snack Food Packaging Waste as a Sound-Absorbing Composite Material in Buildings Exposed to Sound Pollution - Chandra Halim.M (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
Until now, the conventional problem encountered, namely waste, is still a problem that worsens the environmental conditions of society in Indonesia. Starting from inorganic waste such as plastic to organic waste such as vegetable and fruit waste, it has the same role in reducing the quality of public health. plastic is waste that takes a long time to decompose so that plastic waste is one of the most crucial problems in the current era. One way is to make it an environmentally friendly product, such as the development of absorbent materials or sound absorbers by utilizing plastic waste. Sound pollution is the propagation of noise with ranging impact to the human life. Sound pollution is produced by machines, transport and propagation systems which frequently places in urban area. Sound pollution can lead to the psychological issue and physical issue such as cardiovascular effects and corona artery disease due to the sound intensity. This discussion will focus on plastic snack heaters, namely LDPE (Low Density Polyethylene) plastic. In this research, the community is expected to be able to use plastic waste into goods or products that are more useful to reduce the number of inorganic waste. The research method are literature study which used as the fundamental comprehension to do the plastic waste and composite material research also an experimental method by making four types of panel samples of various plastic waste processing. Comparison variations in the form of differences in the size of plastic pieces 0.5 cm x 0,5 cm, 1 cm x 1 cm and 1,5 cm x 1,5 cm and processed tapioca flour without the addition of pieces of plastic waste that will be tested at sound frequencies 400 Hz, 600 Hz, 800 Hz, 1000 Hz, and 1200 Hz. Â From all calculation, It obtains that all variation works perfectly in range frequency 400 â€“ 600 Hz. For 800, 1000 and 1200 there are mines coefficient that informs the increasing of sound intensity level instead of reducing noises. For the size, as the pieces of plastic snack packaging food waste size grows up, the better quality of plastic waste composite material gained. It can be investigated in 1 cm x 1 cm and 1,5 cm x 1,5 cm size which almost all appears the positive value of the coefficient of sound absorption. The condition is totally opposite with control and 0,5 cm x 0,5 cm. As the smaller pieces or non pieces, the sound can still propagate easily through the pipe without any obstacles. On the other hand, for 1 cm x 1 cm and 1,5 cm x 1,5 cm size, the sound can not propagate easily through the sample since there are big plastic waste which absorbs the sound. Therefore, the best variations are 1 cm x 1 cm and 1,5 cm x 1,5 cm. By applying regression linear to prove the highest coefficient determination and the equation. By applying the regression linear into 1 cm x 1 cm and 1,5 cm x 1,5 cm, the equation obtained y = -3,258 ln (x) + 22,163 with coefficient determination (R2) = 0,6304 and y = -2,516 ln (x) + 14,627 with coefficient determination (R2) = 0,5102. These variations show the decrease exponential by 1 cm x 1 cm is the lowest gradientÂ m = -3,258 compared to the 1,5 cm x 1,5 cm which has gradient m = -2,516. As the lower gradient indicates the higher absorption of noise. On the other hand, The coefficient determination is mathematical tools to indicate how the impact of independent variable for dependent variable. From those calculations, it concludes that the best variation for coefficient of sound absorption parameter and statistical calculation is 1 cm x 1 cm by having R2 equal 0,6304 compared to the 1,5 cm x 1,5 cm which has R2 equal 0,5102. It also strongly proves that plastic snack packaging food waste can be one of the material composite by applying 1 cm x 1 cm around of frequency 400-600 Hz.